The role of meiofauna in the nitrogen cycle of a cold marine mesocosm. - Parent, Serge. (University of Ottawa (Canada), 1999)
The nitrogen cycle is the key process in marine mesocosms. This cycle involves mineralizing and nitrifying bacteria which are preyed upon by meiofauna. Large populations of meiofauna (20--40 g·m--2 in the top 2.5 cm of sand) are found in the sand filters of the St. Lawrence marine mesocosm at the Montreal Biodome. A nitrogen budget was prepared for 1995 to quantify the importance of mineralization and nitrification in the mesocosm. Of the input nitrogen, 15% to 31% were transformed into ammonia through bacterial mineralization, and 71% passed through the nitrification process. Filtration and cleaning removed 20% of the input nitrogen, and only 5% were transformed into animal biomass. Experiments were then conducted in microcosms to see how filter meiofauna affect the apparent mineralization rate (AMR) and apparent nitrification rate (ANR). Microfauna and meiofauna abundances were manipulated to quantify their effect on AMR and ANR by linear regression analysis. Harpacticoid copepods dominated in number (87%) and biomass (98%). Neither AMR nor ANR were related to microfauna densities. AMR was inversely related to meiofaunal mass. Particle size affected the effect of meiofauna whereas the C:N ratio affected the AMR0, i.e. the AMR in absence of meiofauna. Meiofauna biomass had no effect on nitrition but had a variable effect on nitration. This effect varied from --20% to +571%. The slope of the ANR vs Meiofauna regression was related to the particulate organic nitrogen content of the sediment. Meiofauna seems to exert a direct action by preying on nitrifiers and an indirect action by reducing the mineralizing bacteria through grazing. Results suggest that meiofauna plays an important role in water treatment by reducing the production of nitrate and more rapidly eliminating nitrite which are toxic to fish.
Keywords: Biology, Ecology.